Index of Undergraduate Students’ Attitude towards Scientific Research: A Study in Peru and Spain - Hernández, R. M.; Saavedra-López, M. A.; Calle-Ramirez, X. M.; Rodríguez-Fuentes, A. (Jurnal Pendidikan IPA Indonesia, 2021)
The aim of this research was to determine the attitude towards scientific research in undergraduate university students from Peru and Spain. The research was descriptive, comparative and cross-sectional. The sample consisted of 953 undergraduate students currently enrolled in universities in Spain (485) and Peru (468), and the information was collected through convenience sampling. The General Index of Attitude towards Research instrument was applied, which was adapted for the study. Its statistical validation was carried out and high reliability of the instrument was proved with a Cronbach's Alpha of 921. According to the questionnaire scores, a sociodemographic survey was also applied. Regarding the results, it was found that students from Peru have a high predisposition towards research (51.5%) compared to students from Spain (23.5%). Regarding knowledge about research, students in both countries recognize that scientific research is not adequately valued (60.6% in Spain and 54.3% in Peru); however, they would like to carry out educational scientific research (63.3% and 71.2, respectively). Regarding the evaluation of the quality of university education, undergraduate students from Spain perceive a better quality in their education (7.22 out of 10), quality of the program in which they are enrolled (7.31 out of 10), quality of fellow students (7.46 out of 10), and welfare and infrastructure services (7.30 out of 10). It is concluded that students from Peru show a better attitude towards research (M=28.98, DT=10.26) than students from Spain (M=22.61, DT=8.28).